The roles and functions of Cantonese Daoist priests (Daoshi) in Kuala Lumpur, Malaysia / Wu Mun Yu - Wu, Mun Yu (1994)
This project paper, comprising five chapters, tries to give a general picture of daoist priests in Malaysia, in particular their roles as Chinese religious special list. In the first chapter, the scope of this project is briefly discussed and some relevant works are reviewed too. Then, one can also find the definition of daoist priests and the rites they conduct too. In addition, the historical background of the Daoist religion as well a the research methodology are described. In the second chapter, I discuss the background of daoist priests and try to look in to the organizational aspects of the daoist priests by referring to their relations hip withother parties concerned and their apprenticeship. In Chapter 3, the roles and functions of daoist priests are exam I need and in Chapter 4. the focus is on the various rites, in connection to death, conducted by daoist priests. Finally, a conclusion is drawn in Chapter 5 and we shall see the significance of daoist priests in Chinese community and Chinese Religion in Malaysia.